Digital Municipality: Deploying a Mobile Platform for Integrated Online Municipal Services in Nepal’s Local Governments - Bhatt, Birendra Prasad (The Management Review, 2026)
The purpose of this study is to propose a mobile-first architecture that integrates vital municipal services within local governments in Nepal. While there is increased focus on digitizing services through the Government of Nepal’s Digital Nepal Framework, most municipalities continue to rely on fragmented and paper-intensive procedures. This research involved conducting semi-structured interviews and surveys with the IT staff of seven local government organizations in Kanchanpur District (two rural municipalities and five municipalities). This research analyzed the findings using the Design Science Research approach and the SDLC model to identify the requirements and develop a viable architecture for the proposed information system. A relational database, micro service architecture, and security mechanisms like role-based access control and OAuth2/JWT are essential features that make this proposal possible. A few critical outcomes from the research suggest that such architectural designs help reduce costs, enhance transparency, and improve service delivery, particularly in disconnected regions by leveraging offline caching. This report is an informative resource for local governments wishing to implement effective e-governance systems centered on their citizenry. It demonstrates how municipalities can achieve digital transformation that is both scalable and sustainable along with the practical implementation of the Digital Nepal Framework.